PHYSICOCHEMICAL PROPERTIES AND PERIPHYTIC ALGAE OF IKOT EBAK RIVER, ESSIEN UDIM LGA, AKWA IBOM STATE - Denise, E. M.; Okhator, Osagie; Affah, G. P.; Anyadike, M. C. (FUDMA JOURNAL OF SCIENCES, 2022)
Periphyton constitutes one of the primary sources of energy in the aquatic food chain in streams, rivers and lakes. They play important role in regulating carbon and nutrient cycling. They are also used in many studies as pollution index organisms. A survey of Periphytic algae in Ikot Ebak River was investigated between October 2019 and February 2020. Samples were collected monthly for physicochemical analysis and periphyton studies. Water samples for physical and chemical parameters were collected directly into transparent plastic containers, while periphyton samples were scraped from the surface of leaves, stems, and roots of aquatic macrophytes, dead and felled logs submerged on the banks of rivers, including the rocks embedded in the substratum. The physicochemical parameters such as pH, temperature, conductivity, total suspended solids (TSS), total dissolved solids (TDS) and dissolved oxygen (DO) showed seasonal patterns and qualitative variations in all the stations. A total of 106 taxa of periphytic algae were identified and grouped into four (4) divisions namely; Chlorophyta (64%), Bacillariophyta (19%), Cyanophyta (8%) and Euglenophyta (9%). There was no significant variation between the algal divisions and across the locations (p < 0.05). The Periphytic green algae compositions were dominated by desmids which play a significanct role in pollution monitoring along the coast of the river. The presence of diatoms (Bacillariophyta) and Euglena serves as an indicator that the river is perturbed with organic materials, also Oscillatoria (Cyanobacteria) denotes nutrient enrichment of the river